(untitled) (Proceedings of International Conference on Special Education, 2015)
This paper discusses the level of resilient among gifted and talented students in Malaysia. The level of high resilient will be impact on the social and academic. The concept of this paper aims to identify the extent level of resilient among gifted and talented students to achieve excellent academic results. Many gifted and talented students plagued with various problems concerning environment and everyday life such as social and environmental problems, peer and social culture, followed by issues of social activity lessons, future career, and entertainment, in addition, alot of problems such as food service and social relations with peers in hostels. Resilient is individual skill to be able to adapt in the face of the social environment and the learning environment so that it can be calm and give motivation in academic achievement. Previous studies found resilient can be to the impact on the lives among gifted and talented students. When individuals have the levels of high resilient will be able to face and solve the problems encountered in everyday life. This showed that the resilient can be increased to achieve individual skills in dealing with problems in themselves and others. Therefore, the authors recommend that the actual research to identify issues for understanding resilience among gifted and talented students.